Sustainable housing financing model to reduce South Africa housing deficit. Issue 3 (5th June 2017) - Ganiyu, Bashir Olanrewaju; Fapohunda, Julius Ayodeji; Haldenwang, Rainer
Abstract : Purpose: This study aims to identify and establish effective housing financing concepts to be adopted by government in achieving its mandate of providing sustainable affordable housing for the poor to decrease the building of shacks, as well as proposing solutions to the housing deficit in South Africa. A rise in demand and shortage in supply of housing calls for the need to address issues of affordable housing in South Africa, and developing countries in general, to ensure a stable and promising future for poor families. Design/methodology/approach: Literature has revealed that the South African government, at all levels, accorded high priority to the provision of low-cost housing. Thus, government has adopted subsidy payment as a method of financing affordable housing to ensure that houses are allocated free to the beneficiaries. This also addresses the historically race-based inequalities of the past, but unfortunately, this has not been fully realised. This study uses a sequential mixed method approach, where private housing developers and general building contractors were the research participants. The qualitative data were analysed using a case-by-case analysis, and quantitative data were analysed using a descriptive statistical technique on SPSS. Findings: The results of the qualitative analysis reveal a gross abuse of the housing subsidies system by the beneficiaries of government-funded housing in South Africa. This is evident from illegal sale of the houses below market value. This has led to a continual building of shacks and an increased number of people on the housing waiting list instead of a decrease in the housing deficit. The results from quantitative analysis affirm the use of "Mortgage Payment Subsidies, Mortgage Payment Deductions, Down-Payment Grant and Mortgage Interest Deductions" as viable alternatives to subsidy payment currently in use to finance affordable housing projects by the South African Government. Practical implications: At the moment, the focus of the South African National Government is continual provision of free housing to the historically disadvantage citizens, but the housing financing method being used encourages unapproved transfer of ownership in the affordable housing sector. This study thus recommends the use of an all-inclusive housing financing method that requires a monetary contribution from the beneficiaries to enable them take control of the process. Originality/value: The relational interface model proposed in this study will reduce pressure on government budgetary provision for housing and guarantee quick return of private developers' investment in housing. Government must, as a matter of urgency, launch a continuous awareness programme to educate the low-income population on the value and the long-term benefits of the housing.